Conjugate Addition of Indoles with 1,5-Diaryl-1,4- pentadien-3-ones Catalyzed by Molecular Iodine under Ultrasound Irradiation - LI, JI-TAI; LIN, ZHI-PING (Asian Journal of Chemistry, 2010)
The conjugate addition of indoles with 1,5-diaryl-1,4- pentadien-3-ones catalyzed by molecular iodine afforded the corresponding products in moderate to good yields under ultrasound irradiation at room temperature within 40-90 min.